Non-linear association between serum folate concentrations and dyslipidemia: Korea National Health and Nutrition Examination Survey 2016-2018 - Taiyue Jin; Eun Young Park; Byungmi Kim; Jin-Kyoung Oh (Epidemiology and Health, 2022)
OBJECTIVES We aimed to evaluate the association between serum folate concentrations and the prevalence of dyslipidemia. METHODS A total of 4,477 adults (2,019 male and 2,458 female) enrolled in the Korea National Health and Nutrition Examination Survey (KNHANES) 2016-2018 were included. Serum samples were used to assess folate concentrations and total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL)-cholesterol, and high-density lipoprotein (HDL)-cholesterol levels. Multivariate logistic regression with sampling weights was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs). RESULTS Elevated TC, TG, LDL-cholesterol and HDL-cholesterol levels were observed in 506 (11.3%), 646 (14.4%), 434 (9.7%), and 767 (17.1%) participants, respectively. We found non-linear trends between serum folate concentrations and the prevalence of hypercholesterolemia and hyper-LDL cholesterolemia from the restricted cubic smoothing spline. A higher prevalence of hypercholesterolemia was observed among participants in the first tertile of serum folate concentrations (OR,1.38; 95% CI, 1.05 to 1.79) than among those in the second tertile. However, a higher prevalence of hyper-LDL cholesterolemia was identified for both the first and third serum folate concentration tertiles (OR, 1.49; 95% CI, 1.08 to 2.05 and OR, 1.63; 95% CI, 1.20 to 2.20, respectively); furthermore, in these tertiles, the prevalence of hyper-LDL cholesterolemia was more pronounced among obese participants. CONCLUSIONS Non-linear associations may exist between serum folate concentrations and the prevalence of hypercholesterolemia and hyper-LDL cholesterolemia in adults. The findings suggest that more accurate recommendations about folate intake and folic acid fortification and supplementation should be provided.